The impact of the COVID-19 pandemic on the incidence of myocardial infarctions: an overview of current research - Jakub Roman; Daniel Gondko; Patrycja Dębiec; Nikodem Pietrzak (Kazimierz Wielki University, 2024)
Introduction and Purpose: The COVID-19 pandemic has posed significant challenges to healthcare systems worldwide, particularly impacting the management of critical non-COVID conditions such as myocardial infarction (MI). This review aims to explore the alterations in the management of MI during the pandemic and assess how these changes have influenced patient outcomes. State of Knowledge: Numerous studies have reported delays in MI treatment during the pandemic due to healthcare resource reallocation towards COVID-19 care and patient hesitance in seeking timely medical help. Innovations such as telemedicine have been integrated into patient care to overcome barriers. However, these changes have varied impacts on clinical outcomes, including increased mortality and complication rates among MI patients during the pandemic. This review consolidates findings from recent studies focusing on altered treatment protocols, patient care strategies, and overall health system response during this period. Summary: The management of myocardial infarction during the COVID-19 pandemic has witnessed substantial shifts, leading to both challenges and innovations in cardiac care. While some adjustments have provided temporary solutions, the overall impact on MI outcomes has highlighted the need for more resilient healthcare strategies that ensure the continuity of care for acute cardiac events during global health emergencies.